Prognostic Value of Lymph Node Ratio in Comparison to Lymph Node Metastases in Stage III Colon Cancer - Zare Mirzaei, Ali (Iran J Pathol, 2015)
BACKGROUND & OBJECTIVES: Colon cancer is currently of high incidence and mortality rate. Identifying the factors influencing its prognosis can be very beneficial to its clinical treatment. Recent studies have shown that lymph nodes ratio can be considered as an important prognostic factor. The aim of the present study is to investigate the effect of this factor on the prognosis of the patients presenting with stage III colon cancer and to compare the result with the effect of lymph node stage on their prognosis. MATERIALS: This cross-sectional study was carried out on 66 patients of stage III colon cancer, who met the study inclusion criteria. Patients were categorized into four groups based on Kaplan-Meier plots: LNR1 0-12%, LNR2 13-40%, LNR3 41-84% and LNR4 85-100%. Survival was estimated by Kaplan-Meier method, and differences analyzed by Log-rank test. A Cox proportional hazards model was used for multivariate analysis. RESULTS: Lymph nodes ratio was a significantly variable both in overall survival ( P <0.0001) and in disease-free survival ( P =0.009). Lymph node stage was significant in overall survival ( P =0.008) but not in disease-free survival ( P =0.05). Multivariable analysis of overall survival showed lymph nodes ratio as the only independent prognostic factor. CONCLUSION: Lymph node ratio is a more accurate prognostic factor than lymph node stage in overall survival and, in particular, in disease-free survival in patients with stage III colon cancer.